Adult height and the risks of cardiovascular disease and major causes of death in the Asia-Pacific region: 21,000 deaths in 510,000 men and women. - Lee, C; Barzi, F; Woodward, M; Batty, G; Giles, G; Wong, J; Jamrozik, K; Lam, T; Ueshima, H; Kim, H; Gu, D; Schooling, M; et al. (2009)
BACKGROUND: In Caucasian populations, adult height is inversely associated with cardiovascular disease (CVD) risk and positively related to some cancers. However, there are few data from Asian populations and from women. We sought to determine the sex- and region-specific associations between height and cardiovascular outcomes, and deaths due to cancer, respiratory and injury in populations from the Asia-Pacific region. METHODS: Thirty-nine studies from the Asia Pacific Cohort Studies Collaboration database were included. We used Cox proportional hazard regression models to estimate the associations between height and pre-specified outcomes. RESULTS: A total of 510,800 participants with 21,623 deaths were included. Amongst men, inverse linear associations were observed between height and coronary heart disease (CHD), stroke, CVD, injury and total mortality. The hazard ratios [95% confidence intervals, (CI)] for a 1-SD (= 6 cm) increment in height ranged from 0.85 (0.80-0.91) for injury to 0.97 (0.95-0.98) for total mortality. Similar trends were found between height and CHD, haemorrhagic stroke and CVD in women. A positive linear association was observed between height and cancer mortality. For each standard deviation greater height, the risk of cancer was increased by 5% (2-8%) and 9% (5-14%) in men and women, respectively. No regional difference was observed between Asian and Australasian cohorts. Adjusting for markers of education did not alter the results. CONCLUSIONS: The opposing relationships of height with CVD and cancer suggest that care is required in setting national policies on childhood nutrition lest they have unintended consequences on the incidence of major non-communicable diseases.